Monitoring of anthropometric parameters of 16-18 Year Olds - Elmazi, Rovena; Kushta, Entela; Mara, Ferdinand; AnduelaLile, AnduelaLile; Pogoni, Junida; Çobaj, Jorida; Xhebexhiu, Klajdi (Edelweiss Applied Science and Technology, 2025)
The development of health and performance-related physical fitness components during the early stages of life has an important impact on maintaining a sustainable level of physical fitness and improving health outcomes in the future, according to many studies. This study aims to analyze anthropometric parameters and physical activity levels in Albanian adolescents aged 16-18 years, making a comparison between urban and rural areas. Physical activity during this period of life is essential for physical and psychological well-being, as well as for the development of executive and cognitive functions. The study included 1,147 students from different schools in Albania and relied on mixed research methods, combining quantitative and qualitative analyses. Anthropometric measurements were performed according to international standards, including height, weight, and body mass index (BMI). The results show that 68.2% of the participants had a normal BMI, while the prevalence of underweight was higher in rural areas (20.6%) than in urban areas (16.8%). Meanwhile, overweight and obesity were more prevalent in urban areas. The findings suggest the need for policies focused on promoting physical activity and health education in both areas to ensure healthy youth development.